Technical efficiency and its determinants in household pig production in Vietnam: A DEA approach - Nguyen Thi Ly; Nanseki, T.; Chomei, Y. (Agricultural Economics Society of Japan, 2016)
Using a two-stage approach with an input-oriented DEA model, this study investigates technical efficiency in household pig production in Vietnam and seeks to determine which factors affect it. The results show that overall technical efficiency (TEcrs) was 80.40%. It is further found that households' poor management, rather than their operating scales, prevented technical efficiency from reaching its full potential. Factors affecting on TEcrs include live weight per fattening pig, breeding time, experience, education, family member joining in pig production, income from pig, access to credit and veterinary services. Thus, potential means of improving technical efficiency in pig production are suggested and thereby enhancing Vietnamese households' performance.